2023
DOI: 10.1200/jco.2023.41.16_suppl.12005
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blind, placebo-controlled study of topical diclofenac in prevention of hand-foot syndrome in patients receiving capecitabine.

Abstract: 12005 Background: Capecitabine induced HFS is associated with deterioration of quality of life of patients and dose of capecitabine is often reduced to manage this adverse event. Celecoxib is the only effective intervention in preventing HFS; however, its widespread use is limited due to its own safety concerns. We conducted this study to assess the efficacy of topical diclofenac in preventing capecitabine induced HFS. Methods: Patients with breast and gastrointestinal (GI) cancers, planned for capecitabine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, it is known that damage to the vascular endothelia in the hands and feet leads to an inflammatory reaction. Hence, there is data regarding the use of NSAIDs, such as topical diclofenac, for preventing HFS 15 . Previous studies found data about the predictors for the development of HFS that including concurrent administration of capecitabine with renin-angiotensin system inhibitors, high body surface area, and low albumin levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that damage to the vascular endothelia in the hands and feet leads to an inflammatory reaction. Hence, there is data regarding the use of NSAIDs, such as topical diclofenac, for preventing HFS 15 . Previous studies found data about the predictors for the development of HFS that including concurrent administration of capecitabine with renin-angiotensin system inhibitors, high body surface area, and low albumin levels.…”
Section: Introductionmentioning
confidence: 99%